Proceedings of the 37th International Symposium on Automation and Robotics in Construction (ISARC) 2020
DOI: 10.22260/isarc2020/0071
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Control of 5-DoF Boom Crane

Abstract: Automation of cranes can have a direct impact on the productivity of construction projects. In this paper, we focus on the control of one of the most used cranes, the boom crane. Tower cranes and overhead cranes have been widely studied in the literature, whereas the control of boom cranes has been investigated only by a few works. Typically, these works make use of simple models making use of a large number of simplifying assumptions (e.g. fixed length cable, assuming certain dynamics are uncoupled, etc.) A f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The 3D models of the double spherical 3D pendulum studied in the works [34][35][36][37] are more advanced. However, loads of point mass, not of distributed mass, are considered in these works.…”
Section: Literature Review and Problem State-mentmentioning
confidence: 99%
“…The 3D models of the double spherical 3D pendulum studied in the works [34][35][36][37] are more advanced. However, loads of point mass, not of distributed mass, are considered in these works.…”
Section: Literature Review and Problem State-mentmentioning
confidence: 99%
“…Solving (18) for the multipliers 𝜆, we obtain 𝜆 = (A(q)B(q) −1 A(q) T ) −1 (A(q)B(q) −1 (C(q, q) q + g(q) − Su) − Ȧ(q, q) q). (…”
Section: Modeling Of Robotic Systemmentioning
confidence: 99%
“…In the authors designed a Proportional-Derivative (PD) controller with gravity compensation based on the nonlinear model of the boom crane. In (Ambrosino, Berneman, et al, 2020) is shown a partial feedback linearization (PFL) based on detailed mathematical model of boom cranes. In (Uchiyama, Takagi, & Sano, 2006) is shown a pole placement approach for a linearized model of boom crane.…”
Section: Introductionmentioning
confidence: 99%